A RARE CASE OF THYROTOXICOSIS PRESENTING AS HYPERBILIRUBINAEMIA - Mok, Meng Loong; Rajoo, Subashini; Teoh, Pei Yeing; Sallapan, Sugunah (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hyperthyroidism affects multiple body systems, including the nervous, cardiovascular, gastrointestinal, and hepatobiliary systems. Presentation of severe cholestatic jaundice in thyrotoxicosis, although uncommon, has been described in literature. CASE A 28-year-old Malay male presented with 1-week history of painless jaundice, associated with tea-coloured urine and diarrhoea. He also had a significant weight loss of 12 kg over the past 10 months. Physical examination showed an underweight young male, deeply jaundiced, with fine tremors. He was normotensive and not tachycardic. He did not have a goitre, thyroid eye disease or pretibial myxoedema. He had no stigmata of chronic liver disease. Blood investigation showed transaminitis with conjugated hyperbilirubinemia, with ALT 174 IU/L, AST 112 IU/L, total bilirubin 357 µmol/L, and predominant direct bilirubin (252 µmol/L). Autoimmune, infectious, and primary hepatobiliary disorders were ruled out. Thyroid function test was taken on day 16 of admission, which showed suppressed TSH <0.01 m IU/L, and elevated free T4 at 77 pmol/L. He was started on carbimazole, prednisolone and cholestyramine. carbimazole was withheld after 1 week of treatment in view of worsening hyperbilirubinemia and transaminitis. Subsequently, he received radioactive iodine therapy after 3 weeks of treatment. He had clinical and biochemical improvement after the radioactive iodine therapy. He eventually progressed into a hypothyroid state. His bilirubin levels subsequently normalized. CONCLUSION Severe jaundice is a rare consequence of hyperthyroidism and can be due to various pathologies. A thorough investigation should be done to look for contributing factors and hence, be treated accordingly. Treatment of hyperthyroid patients with liver abnormalities is rather challenging as antithyroid drugs have been associated with liver injury. Various case reports showed remission of hyperbilirubinemia after radioactive iodine therapy. Therefore, radioactive iodine therapy should be offered as early as possible for patients with severe hyperbilirubinemia that is likely due to hyperthyroidism.